Composite material for polishing, preparation method of composite material and polishing pad

By using composite materials of polyurethane and nonwoven fabrics and combining post-crosslinking technology, the problems of complex preparation and compatibility of existing polishing pads are solved, and a polishing pad with high hardness, good compression rate and uniformity are achieved, which improves the polishing performance.

CN119800717APending Publication Date: 2025-04-11BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411426176.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

When existing polishing pads take into account both hardness and compression ratio, the preparation process is complex and compatibility is difficult to ensure, resulting in uneven polishing performance.

Method used

By using a composite material formed by polyurethane and nonwoven fabric, the polyurethane is prepared by reacting diisocyanate, polyether polyol and crosslinking agent, and impregnating with the nonwoven fabric by post-crosslinking method to form a polishing pad with high hardness and good compression.

Benefits of technology

The high hardness, good compression rate and uniformity of the polishing pad are achieved, the preparation process is simplified, and the polishing performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800717A_ABST
    Figure CN119800717A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a composite material for polishing, a preparation method of the composite material and a polishing pad. The composite material for polishing comprises a composite material formed by polyurethane and a non-woven fabric, the polyurethane is prepared through reaction of diisocyanate, polyether polyol and a cross-linking agent, and the polyether polyol comprises polyether polyol with the number-average molecular weight smaller than or equal to 500 g / mol. The composite material for polishing provided by the embodiment of the invention has relatively high hardness and good compression ratio, and can be used for providing a polishing pad with relatively high hardness, good compression performance and relatively high uniformity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polymer materials, and in particular to a composite material for polishing, a preparation method thereof, and a polishing pad. Background Art

[0002] In the semiconductor industry, the surface treatment of wafers is very important. At present, the mainstream technology for wafer surface flattening is chemical mechanical polishing, and the performance of the polishing pad used in the above process is very critical. Polishing pads commonly used in the industry include polyurethane polishing pads, such as foamed and non-woven composite types. In the related art, in order to take into account the elasticity and hardness of non-woven polyurethane polishing pads, it is usually dependent on the composite of polyurethane and other resins. In this way, not only is the preparation process complicated, but also the compatibility of different resins with non-woven fabrics needs to be considered. Summary of the invention

[0003] In view of this, the present invention provides a polishing composite material and a preparation method thereof, and a polishing pad. The polishing composite material provided in the present invention has high hardness and good compressibility, and can be used to provide a polishing pad with high hardness, good compression performance and high uniformity.

[0004] A first aspect of an embodiment of the present application provides a composite material for polishing, wherein the composite material for polishing includes a composite material formed by polyurethane and non-woven fabric, wherein the polyurethane is prepared by reacting diisocyanate, polyether polyol and a cross-linking agent, and the polyether polyol includes a polyether polyol with a number average molecular weight ≤500g / mol.

[0005] The soft segment in the molecular chain of the polishing composite material polyurethane provided in the embodiment of the present application includes a segment structure obtained by reacting a polyether polyol having a number average molecular weight ≤500g / mol with an isocyanate group. Therefore, the molecular segment length of the soft segment in its molecular chain is relatively short, thereby increasing the proportion of the hard segment in the molecule. Furthermore, by adding a cross-linking agent to the system for cross-linking, the rigidity of the polyurethane can be effectively improved.

[0006] A second aspect of the embodiment of the present application provides a method for preparing a composite material for polishing, comprising:

[0007] Mixing diisocyanate, polyether polyol and solvent to obtain a first mixture, and reacting at a first temperature for a first time to obtain a solution containing a first prepolymer; the polyether polyol includes a polyether polyol having a number average molecular weight of ≤500 g / mol;

[0008] adding a crosslinking agent to the solution containing the first prepolymer to obtain a second mixture;

[0009] The non-woven fabric is placed in the second mixture and dried at a second temperature to obtain a composite material for polishing.

[0010] The polyurethane in the polishing composite material of the above preparation method adopts a post-crosslinking method, that is, the non-woven fabric fibers are impregnated with a mixture of a low-viscosity thermoplastic polyurethane solution and a crosslinking agent, which can make the impregnation more uniform; the polyurethane solution used for impregnation is a mixture of a hydroxyl-terminated prepolymer and a crosslinking agent, which reduces the difficulty of non-woven fabric impregnation molding and solves the problem of unstable storage of isocyanate-terminated polyurethane. The final polishing composite material can have high hardness, good compressibility and high uniformity.

[0011] The third aspect of the embodiment of the present application provides a polishing pad, the polishing pad comprises a polishing layer, and the polishing layer comprises a composite material for polishing. The polishing pad provided by the present application has good polishing performance during the chemical mechanical polishing process. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1A and Figure 1B They are respectively a surface scanning electron microscope (SEM) photograph and a cross-sectional SEM photograph of the polishing composite material prepared in Example 5;

[0013] Figure 2 This is a surface photograph of a silicon carbide wafer polished by the polishing composite material of Example 1;

[0014] Figure 3 This is a photograph of the polishing composite material of Example 1 during polishing of a silicon carbide wafer; DETAILED DESCRIPTION

[0015] An embodiment of the present application provides a composite material for polishing, which includes a composite material formed by polyurethane and non-woven fabric, wherein the polyurethane is prepared by reacting diisocyanate, polyether polyol and a cross-linking agent, and the polyether polyol includes a polyether polyol with a number average molecular weight of ≤500g / mol.

[0016] The soft segment in the molecular chain of the polishing composite material polyurethane provided in the embodiment of the present application includes a segment structure obtained by reacting a polyether polyol having a number average molecular weight ≤500g / mol with an isocyanate group. Therefore, the molecular segment length of the soft segment in its molecular chain is relatively short, thereby increasing the proportion of the hard segment in the molecule. Furthermore, by adding a cross-linking agent to the system for cross-linking, the rigidity of the polyurethane can be effectively improved.

[0017] In the embodiments of the present application, polyurethane refers to a polymer containing a carbamate group (-NHCOO-) in its molecular structure. It can be understood that the molecular structure of polyurethane includes a soft segment and a hard segment, the soft segment can give polyurethane a certain elasticity, and the hard segment can give polyurethane hardness.

[0018] The polyurethane in the polishing composite material provided by the embodiment of the present application has a high number average molecular weight and a narrow molecular weight distribution, and there is no low molecular weight segment that affects the mechanical properties of the polyurethane, so the polyurethane can have a high hardness. In addition, the soft segment in the polyurethane molecular chain includes a segment structure obtained by reacting a polyether polyol with a number average molecular weight of ≤500g / mol with an isocyanate group, so the molecular segment length of the soft segment in its molecular chain is short, which can effectively improve the rigidity of the polyurethane, and can be used to provide a polishing composite material with both high hardness and good compression rate.

[0019] In the embodiments of the present application, the number average molecular weight of the polyether polyol with a number average molecular weight ≤ 500 g / mol may be, but is not limited to, 100 g / mol, 200 g / mol, 300 g / mol, 400 g / mol, 500 g / mol, etc.

[0020] In some embodiments of the present application, the polyether polyol with a number average molecular weight of ≤500 g / mol includes, but is not limited to, one or more of polytetramethylene glycol (PTMG) and its derivatives, polypropylene glycol (PPG) and its derivatives, polyethylene glycol (PEG) and its derivatives. Specifically, the above-mentioned derivatives of PTMG, derivatives of PPG, and derivatives of PEG can be PTMG, PPG, and PEG substituted with substituents, respectively; the above-mentioned substituents are independently selected from amine groups, halogen atoms, etc.

[0021] For the convenience of description, the polyether polyol with a number average molecular weight of ≤500g / mol is referred to as "low molecular weight polyether polyol" hereinafter, and the polyether polyol with a number average molecular weight>500g / mol is referred to as "high molecular weight polyether polyol". In some other embodiments of the present application, the above-mentioned polyether polyol includes the above-mentioned low molecular weight polyether polyol and high molecular weight polyether polyol, and the mass proportion of the low molecular weight polyether polyol in the polyether polyol is ≥50%. In this way, the average chain length of the soft segment in the molecular structure of the highly wear-resistant polyurethane can also be controlled to be shorter, and the hardness of the polyurethane can be made higher. Specifically, the mass proportion of the above-mentioned low molecular weight polyether polyol in the polyether polyol can be, for example, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, etc.

[0022] In some embodiments of the present application, diisocyanates include, but are not limited to, one or more of 4,4'-diphenylmethane diisocyanate (4,4'-MDI) or its derivatives, 2,4'-diphenylmethane diisocyanate (2,4'-MDI) or its derivatives, 2,2'-diphenylmethane diisocyanate (2,2'-MDI) or its derivatives, meta-xylylene diisocyanate (XDI) or its derivatives, 1,5-naphthalene diisocyanate (NDI) or its derivatives. In this way, the polyurethane has good processability, which is beneficial to its subsequent application.

[0023] In some embodiments of the present application, based on the total mass of the polishing composite material, the mass proportion of the polyurethane is 40% to 85%, the mass proportion of the non-woven fabric is 15% to 60%, and the mass proportion of the cross-linking agent is 2% to 10% of the polyurethane. Polyurethane as the main component accounts for 40% to 85%, which can enable the composite material to show good elasticity and wear resistance during the polishing process. At the same time, the non-woven fabric is used as a reinforcing material, accounting for 15% to 60%, which not only enhances the overall strength and wear resistance of the composite material, but also improves its tear resistance and wear resistance, effectively extending the service life of the material. It can be understood that the mass proportion of polyurethane in the polishing composite material can be one of 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, and 85%, and the mass proportion of non-woven fabric in the polishing composite material can be one of 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, and 60%.

[0024] In some embodiments of the present application, based on the total mass of the polyurethane, the mass proportion of the crosslinking agent is 2% to 10%. The appropriate amount of crosslinking agent (2% to 10%) further improves the hardness and durability of the composite material by promoting the chemical crosslinking reaction of the polyurethane. Optionally, the mass proportion of the crosslinking agent in the polyurethane can be one of 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, and 10%.

[0025] In some embodiments of the present application, the Shore hardness of the polishing layer is 75A-110A. Specifically, the Shore hardness of the polishing composite material can be, for example, 75A, 80A, 85A, 90A, 95A, 100A, 105A, 110A. In the embodiments of the present application, the Shore hardness of the polishing layer can be tested with reference to GB / T2411-2008 "Determination of indentation hardness (Shore hardness) of plastics and hard rubber using a hardness tester".

[0026] In some embodiments of the present application, the compression rate of the polishing composite material is 1%-15%. The appropriate compression rate is conducive to the storage and transportation of the polishing liquid, and can also effectively avoid the problem of scratching the workpiece surface. Specifically, the compression rate of the polishing composite material can be, for example, 1%, 3%, 5%, 8%, 10%, 12%, 15%. In the embodiments of the present application, the compression rate of the polishing layer can be tested with reference to GB / T24442.1-2009 "Determination of compression properties of textiles Part 1: Constant method".

[0027] In some embodiments of the present application, the water absorption rate of the polishing layer is 100%-300%. In this way, during the application of the composite material for polishing, the polishing layer has a strong ability to carry the polishing liquid. Specifically, the water absorption rate of the polishing layer can be, for example, 100%, 150%, 200%, 250%, 300%. In the embodiments of the present application, the polishing layer can be placed in deionized water and squeezed to absorb water until the weight no longer changes. Water absorption rate = (mass before water absorption - mass after water absorption) / mass before water absorption * 100%.

[0028] In some embodiments of the present application, the surface roughness of the polishing layer is 11 μm-18 μm. In this way, the polishing effect of the polishing composite material is better and it is not easy to damage the surface of the workpiece to be polished. Specifically, the surface roughness of the polishing composite material can be, for example, 11 μm, 15 μm, 18 μm, etc. In the embodiment of the present application, a surface roughness meter can be used to test the surface roughness of the polishing layer.

[0029] In some embodiments of the present application, the thickness of the polishing layer is 1.7 mm to 2.3 mm, which is beneficial to its application and has a longer service life for the polishing composite material.

[0030] In some embodiments of the present application, the crosslinking agent includes a polyisocyanate and / or a derivative of a polyisocyanate, wherein the polyisocyanate includes 4,4′,4″-triphenylmethane triisocyanate. The isocyanate group (-NCO) is a highly active functional group that easily reacts with other compounds containing active hydrogen (such as alcohols, amines, water, etc.). During the crosslinking process, these isocyanate groups can react with functional groups such as hydroxyl groups and amino groups on the polymer chain to form covalent bonds, thereby connecting different polymer chains to form a three-dimensional network structure. Polyisocyanates, especially trifunctional isocyanates such as 4,4′,4″-triphenylmethane triisocyanate, contain multiple isocyanate groups in each molecule. This versatility enables them to react with multiple polymer chains at the same time to form more crosslinking points, thereby significantly improving the crosslinking density and the strength, hardness and other properties of the material.

[0031] The present application also provides a method for preparing a composite material for polishing, comprising:

[0032] S01, mixing diisocyanate, polyether polyol and solvent to obtain a first mixture, reacting at a first temperature for a first time to obtain a solution containing a first prepolymer; the polyether polyol includes a polyether polyol having a number average molecular weight of ≤500 g / mol;

[0033] S02, adding a crosslinking agent to the solution containing the first prepolymer to obtain a second mixture;

[0034] S03, mixing the non-woven fabric with the second mixture, and drying at a second temperature to obtain a composite material for polishing.

[0035] The polyurethane in the polishing composite material of the above preparation method adopts a post-crosslinking method, that is, the non-woven fabric fibers are impregnated with a mixture of a low-viscosity thermoplastic polyurethane solution and a crosslinking agent, which can make the impregnation more uniform; the polyurethane solution used for impregnation is a mixture of a hydroxyl-terminated prepolymer and a crosslinking agent, which reduces the difficulty of non-woven fabric impregnation molding and solves the problem of unstable storage of isocyanate-terminated polyurethane. Finally, the thermosetting polishing composite material formed by crosslinking has higher hardness, certain elasticity and higher uniformity.

[0036] It is understandable that before mixing the diisocyanate, polyether polyol and solvent, the polyether polyol and solvent are subjected to a dehydration treatment, which can be specifically performed by dehydrating the mixture of the polyether polyol and the solvent, using a dehydration method commonly used in the industry, such as keeping the mixture at 100° C. for a certain period of time.

[0037] In the related art, in order to reduce the reaction barrier and accelerate the polymerization reaction, a catalyst is often introduced into the raw materials for preparing polyurethane. However, in the preparation method provided in this embodiment, no catalyst is required, and the viscosity of the system during the reaction is more controllable. The polymerization experiment of the above preparation method has good controllability, less by-products, and the product performance is stable and can be repeatedly achieved.

[0038] In some embodiments of the present application, in step S01, the solvent includes but is not limited to N,N-dimethylformamide or N,N-dimethylacetamide.

[0039] In some embodiments of the present application, in step S01, the first temperature is 50°C-100°C, and the first duration is 1h-3h. A suitable reaction temperature is conducive to the reaction and the reaction rate can be controlled within a suitable range, which is conducive to the control of the reaction process and the viscosity of the system. Specifically, the above-mentioned first temperature can be, for example, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, etc. Specifically, the first duration can be, for example, 1h, 1.5h, 2h, 2.5h, 3h, etc.

[0040] In some embodiments of the present invention, in step S02, the second temperature is 50°C-80°C. This is conducive to the polymerization reaction. Specifically, the second temperature can be, for example, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc.

[0041] In some embodiments of the present application, in step S01, mixing diisocyanate, polyether polyol and solvent includes: mixing polyether polyol and solvent, adding diisocyanate thereto under the conditions of 10°C to 80°C and protective atmosphere. In this way, it is beneficial to improve the uniformity of the system. Specifically, when adding diisocyanate to the mixture of solvent and polyether polyol, the temperature of the system can be, for example, 25°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, etc.

[0042] In some embodiments of the present application, in the first mixture, the molar ratio of isocyanate group to hydroxyl group is (0.8-0.95):1, which is beneficial to the control of subsequent reactions, thereby facilitating the preparation of polyurethane with high molecular weight and narrow molecular weight distribution. Specifically, in the first mixture, the molar ratio of isocyanate group to hydroxyl group can be, for example, 0.8:1, 0.82:1, 0.85:1, 0.87:1, 0.9:1, 0.95:1, etc.

[0043] In some embodiments of the present application, the solid content of the first mixture is 25%-40%. This is conducive to controlling the viscosity of the system within an appropriate range, facilitating the progress and control of the reaction, and thus making it easy to produce polyurethane with a narrow molecular weight distribution. Specifically, the solid content of the first mixture can be, for example, 25%, 32%, 35%, 38%, 40%, etc.

[0044] In the embodiments of the present application, the molar ratio of isocyanate groups to hydroxyl groups in the first mixture and the second mixture can be tested by titration; or, the molar ratio of the above functional groups in the system can be tested by infrared spectroscopy, ultraviolet spectroscopy and the like.

[0045] An embodiment of the present application also provides a polishing pad, comprising a polishing layer; the polishing layer comprises the aforementioned polishing composite material provided in the embodiment of the present application, or comprises a polishing composite material prepared according to the polishing composite material preparation method provided in the embodiment of the present application.

[0046] Due to the use of the polishing composite material provided in the embodiment of the present application, the polishing layer can have higher hardness, good compressibility and higher uniformity.

[0047] In the embodiment of the present application, the polishing layer can be the polishing composite material provided in the present application. The polyurethane in the polishing composite material in this solution is post-crosslinked, and the non-woven fabric fiber is impregnated with a mixture of a low-viscosity thermoplastic polyurethane solution and a crosslinking agent, which can be impregnated more evenly, and the degree of uniform mixing at the microscopic interface and the macroscopic interface is high, which is conducive to improving the performance of the final polishing composite material; in other words, the difficulty of uniform mixing of the two at the microscopic and macroscopic interfaces, the process is simple, and the production cost is low. In one embodiment, the polishing layer can also be a combination of the polishing composite material described in the present application and other materials, such as inorganic fillers, to further improve the performance of the polishing pad.

[0048] In some specific embodiments, after the above-mentioned drying, the polishing layer is further subjected to grinding, groove engraving, forming a glue layer on its surface, cutting and other processes to obtain a polishing pad.

[0049] In some embodiments of the present application, the polishing layer further has a groove structure. The present application embodiment does not impose any restrictions on the shape, size and distribution of the groove structure, which can be determined according to actual production conditions.

[0050] In some embodiments of the present application, in addition to the polishing layer, the polishing pad may also have other layer structures. For example, a glue layer, etc. In some embodiments of the present application, the polishing pad includes a polishing layer and a glue layer stacked in layers, and the glue layer is used to fix the polishing composite material in the polishing device. In the embodiments of the present application, the material and parameters of the glue layer are not limited. Those skilled in the art can make a selection according to actual production conditions.

[0051] In some embodiments of the present application, the parameters and materials of the non-woven fabric are not limited, and any non-woven fabric known in the art that is suitable for polishing composite materials can be used, and the size parameters of the non-woven fabric are determined according to actual production conditions. In some embodiments of the present application, the material of the non-woven fabric includes but is not limited to one or more of polypropylene, polyester, polyamide, polyacrylonitrile, polyethylene, polyvinyl chloride, and viscose fiber.

[0052] In some specific embodiments, the polishing pad is composed of a glue layer and a polishing layer. The polishing pad of the above structure can avoid the problem of uneven polishing caused by reduced interlayer bonding force in the polishing pad of the related art with a multi-layer structure, and does not contain other resins, and is easy to prepare.

[0053] In the embodiment of the present application, the non-woven fabric may be a needle-punched non-woven fabric or a spunlace non-woven fabric.

[0054] The technical solution of the present application is further illustrated by multiple embodiments below.

[0055] Example 1

[0056] The components and weight percentages of the polishing composite material in Example 1 are as follows: 85% polyurethane, 15% non-woven fabric; the mass ratio of the cross-linking agent to the polyurethane is 2%.

[0057] The polyether polyol is 50% of polyethylene glycol (PEG200) with a molecular weight of 200 g / mol and 50% of polytetramethylene glycol (PTMG650) with a molecular weight of 650 g / mol; the diisocyanate is 2,4′-diphenylmethane diisocyanate (2,4′-MDI); the non-woven fabric is a needle-punched polyamide non-woven fabric; and the cross-linking agent is 4,4′,4′-triphenylmethane triisocyanate (TTI).

[0058] Its production process is:

[0059] ①PTMG250 and DMAC solvents were dehydrated under an inert atmosphere (specifically argon).

[0060] ② When the solution temperature in the above step drops to 58°C, add 2,4′-MDI.

[0061] ③ After the addition is completed, react at 60°C for 3 hours to obtain a polyurethane solution for impregnation. In the above reaction, the molar ratio of isocyanate group to hydroxyl group is 0.92, and the solid content of the solution is 38%.

[0062] ④ Add TTI to the above polyurethane solution at room temperature to obtain the impregnation solution.

[0063] ⑤Put the non-woven fabric into the impregnation liquid and make the impregnation liquid fully penetrate the non-woven fabric through continuous squeezing.

[0064] ⑥ Scrape off the excess impregnation liquid on the surface of the impregnated non-woven fabric.

[0065] ⑦ Dry the impregnated non-woven fabric at 120° C. to remove the solvent and obtain a composite material for polishing.

[0066] ⑧ The sheet obtained in the above steps is subjected to surface grinding, groove engraving, back gluing, cutting and other processing steps to obtain a polishing pad.

[0067] Example 2

[0068] Compared with Example 1, the polyurethane is 65%, the non-woven fabric is 35%, and the mass ratio of the crosslinking agent to the polyurethane is 4%; the polyether polyol is 80% of polyethylene glycol (PEG400) with a molecular weight of 400g / mol and 20% of tetrahydrofuran-propylene oxide copolymer glycol with a molecular weight of 1200g / mol; the diisocyanate is 4,4′-MDI; the non-woven fabric is a needle-punched polyester non-woven fabric; the solvent is DMF; the dropping temperature in step 2 is 46°C; the reaction temperature in step 3 is 70°C, the reaction time is 2 hours, the molar ratio of isocyanate group to hydroxyl group in the reaction is 0.9, and the solid content of the solution is 37%; the drying temperature in step 7 is 110°C.

[0069] Example 3

[0070] Compared with Example 1, the polyurethane is 55%, the non-woven fabric is 45%, and the mass ratio of the crosslinking agent to the polyurethane is 4%; the polyether polyol is 80% of polyethylene glycol (PEG200) with a molecular weight of 200g / mol and 20% of tetrahydrofuran-ethylene oxide copolymer with a molecular weight of 1100g / mol; the dibasic isocyanate is a composition of 2,2′-MDI and 4,4′-MDI; the non-woven fabric is a needle-punched polyester non-woven fabric; the solvent is NMP; the dropping temperature in the second step is 55°C; the reaction temperature in the third step is 75°C, the reaction time is 1.5 hours, the molar ratio of isocyanate group to hydroxyl group in the reaction is 0.83, and the solid content of the polyurethane solution is 33%; the drying temperature in the seventh step is 100°C.

[0071] Example 4

[0072] Compared with Example 1, the polyurethane is 40%, the non-woven fabric is 60%, and the mass ratio of the crosslinking agent to the polyurethane is 10%; the polyether polyol is polytetramethylene ether glycol (PTMG250) with a molecular weight of 250g / mol; the dibasic isocyanate is a composition of 4,4′-MDI and NDI; the non-woven fabric is a needle-punched polyester non-woven fabric; the solvent is NMP; the dropping temperature in the second step is 55°C; the reaction temperature in the third step is 85°C, the reaction time is 2.5 hours, the molar ratio of isocyanate group to hydroxyl group in the reaction is 0.95, and the solid content of the polyurethane solution is 30%; the drying temperature in the seventh step is 105°C.

[0073] Example 5

[0074] Compared with Example 1, the polyurethane accounts for 62%, the non-woven fabric accounts for 38%, and the mass ratio of the crosslinking agent to the polyurethane is 7%; the polyether diol is 90% of polytetramethylene ether diol (PTMG250) with a molecular weight of 250g / mol and 10% of polytetramethylene ether diol (PTMG2000) with a molecular weight of 2000g / mol; the dibasic isocyanate is a composition of 2,4′-MDI and 4,4′-MDI; the non-woven fabric is a needle-punched polyester non-woven fabric; the dropping temperature in the second step is 46°C; the reaction temperature in the third step is 65°C, the reaction time is 1.5 hours, the molar ratio of isocyanate group to hydroxyl group in the reaction is 0.86, and the solid content of the polyurethane solution is 31%.

[0075] Example 6

[0076] Compared with Example 1, the polyurethane is 70%, the non-woven fabric is 30%, and the mass ratio of the crosslinking agent to the polyurethane is 5%; the polyether diol is 60% of polytetrahydrofuran ether diol (PTMG250) with a molecular weight of 250g / mol, 20% of polytetrahydrofuran ether diol (PTMG650) with a molecular weight of 650g / mol and 20% of polytetrahydrofuran ether diol (PTMG1200) with a molecular weight of 1200g / mol; the dibasic isocyanate is 2,2′-MDI; the non-woven fabric is a needle-punched polyester non-woven fabric; the solvent is DMF; the dropping temperature in the second step is 50°C; the reaction temperature in the third step is 80°C, the reaction time is 2.5 hours, the molar ratio of isocyanate group to hydroxyl group in the reaction is 0.8, and the solid content of the polyurethane solution is 35%; and the drying temperature in the seventh step is 100°C.

[0077] Comparative Example 1

[0078] Compared to Example 5, no crosslinking agent was added.

[0079] Comparative Example 2

[0080] Compared with Example 5, the polyether diol is polytetramethylene ether diol (PTMG2000) with a molecular weight of 2000 g / mol, and no low molecular weight polyether diol is added.

[0081] Morphology test

[0082] The surface and cross section of the polishing composite material obtained in each embodiment and comparative example were observed under SEM. The surface and cross section SEM photos of the polishing composite material of Example 5 can be found in Figure 1A and Figure 1B .

[0083] Performance Testing

[0084] (1) Referring to GB / T24218.1-2009 "Test methods for textile nonwovens - Part 1: Determination of mass per unit area", the apparent density of the polishing layer was tested; specifically, 5 samples with a size of 300 mm*300 mm were cut from the polishing layer of each embodiment and comparative example, and the apparent density was calculated by measuring the weight per unit area and the thickness, and the average value was obtained; the results are summarized in Table 1.

[0085] (2) The Shore hardness of the polishing layer of each embodiment and comparative example was tested with reference to GB / T2411-2008 "Determination of indentation hardness (Shore hardness) of plastics and hard rubber using a hardness tester". Specifically, multiple polishing layer samples were stacked to make the test thickness greater than 4 mm, and the Shore hardness of five locations was tested using a Shore hardness tester and the average value was taken. The results are summarized in Table 1.

[0086] (3) The compression rates of the polishing layers of the embodiments and comparative examples were tested with reference to GB / T 24442.1-2009 “Determination of compression properties of textiles Part 1: Constant method”. The results are summarized in Table 1.

[0087] (4) The polishing layer of each embodiment and comparative example was placed in deionized water and squeezed to absorb water until the weight no longer changed. Water absorption rate = (mass before water absorption - mass after water absorption) / mass before water absorption * 100%. The results are summarized in Table 1.

[0088] Table 1

[0089]

[0090] Wafer polishing test

[0091] The polishing layer prepared in each embodiment and comparative example is subjected to surface grinding and groove engraving, and a glue layer is formed on one side of the surface to obtain a polishing composite material, and the thickness of the polishing layer in each polishing composite material is controlled to be consistent. The polishing composite materials prepared in each embodiment and comparative example are respectively installed in a polishing device, and the carbon surface or silicon surface of the silicon carbide wafer is continuously polished for 2 hours, and the thickness removal per unit time of each surface of the wafer is tested, which is the removal rate.

[0092] Wafer surface test: A three-dimensional white light profilometer was used to test each surface of the wafer before and after polishing. The results are summarized in Table 2.

[0093] Table 2

[0094]

[0095]

[0096] It can be seen from the results in Tables 1 and 2 that the polishing composite material provided in the embodiments of the present application has high hardness and good compression rate, and the polishing pad made therefrom has good comprehensive performance, high material removal rate, and will not damage the wafer.

[0097] The above is an exemplary embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made thereto without departing from the principles of the present application. These improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. A composite material for polishing, characterized in that: The polishing composite material comprises a composite material formed by polyurethane and non-woven fabric, the polyurethane is prepared by reacting diisocyanate, polyether polyol and a crosslinking agent, and the polyether polyol comprises a polyether polyol with a number average molecular weight of ≤500 g / mol.

2. The composite material for polishing according to claim 1, characterized in that: Based on the total mass of the polishing composite material, the mass of the polyurethane accounts for 40% to 85%, and the mass of the non-woven fabric accounts for 15% to 60%.

3. The composite material for polishing according to claim 1, characterized in that: Based on the total mass of the polyurethane, the mass proportion of the crosslinking agent is 2% to 10%.

4. The composite material for polishing according to claim 1, characterized in that: The Shore hardness of the polishing composite material is 75A-110A; and / or the compressibility of the polishing layer is 1%-15%; And / or, the apparent density of the polishing composite material is 0.31 g / cm 3 -0.55g / cm 3 ; And / or, the surface roughness of the polishing composite material is 11 μm to 18 μm; And / or, the water absorption rate of the polishing composite material is 100%-300%; And / or, the polishing composite material has a thickness of 1.7 mm to 2.3 mm.

5. The composite material for polishing according to claim 1, characterized in that: The mass proportion of the polyether polyol having a number average molecular weight of ≤500 g / mol in the polyether polyol is ≥50%.

6. The composite material for polishing according to claim 1, characterized in that: The crosslinking agent includes polyisocyanate and / or a derivative of polyisocyanate, and the polyisocyanate includes 4,4′,4″-triphenylmethane triisocyanate.

7. A method for preparing a composite material for polishing, characterized in that: include: Mixing diisocyanate, polyether polyol and solvent to obtain a first mixture, and reacting at a first temperature for a first time to obtain a solution containing a first prepolymer; the polyether polyol includes a polyether polyol having a number average molecular weight of ≤500 g / mol; adding a crosslinking agent to the solution containing the first prepolymer to obtain a second mixture; The non-woven fabric is placed in the second mixture and dried at a second temperature to obtain a composite material for polishing.

8. The preparation method according to claim 7, characterized in that: In the first mixture, the molar ratio of isocyanate group to hydroxyl group is (0.8-0.95):1; and the solid content of the first mixture is 25%-40%.

9. The preparation method according to claim 7, characterized in that: The first temperature is 50°C-100°C, and the first time is 1h-3h; And / or, the second temperature is 50°C-80°C.

10. The preparation method according to claim 7, characterized in that: The solvent includes N,N-dimethylformamide or N,N-dimethylacetamide.

11. A polishing pad, characterized in that: The polishing pad comprises a polishing layer, and the polishing layer comprises the polishing composite material according to any one of claims 1 to 6 or a polishing composite material prepared by the method for preparing the polishing composite material according to any one of claims 7 to 9.